IDENTIFIKASI MODEL ANTRIAN BUS RAPID TRANSIT (BRT) PADA HALTE OPERASIONAL BRT SEMARANG - Niken Nindyaiswari; Sugito Sugito; Yuciana Wilandari (Jurnal Gaussian, 2015)
The process of a queue is a process related with the attending of customers in a service facility, standing in line waiting for the service while the servers are busy servicing the other customers, the customers will leave the facility after getting the service. This process is usually happened in the public services such as at the operational shelter of Semarang Bus Rapid Transit (BRT) Semarang. BRT Semarang has 4 departure gates and transit bus stop passed by all of the buses. The BRT does not have special track. It has to pass though the same road as the other kinds of buses. As a result there are queues in some crowded BRT shelters especially at the service in the departure and shelters that are passed through by all BRT or tracks. An effective special queue model is needed to make the service in the departure and transit shelter more effective. Based on the result of the analysis the best queue model is at the departure shelter track I, II, III, and IV they use the same models (M/G/1) (GD/∞/∞) and the queue models at the City Hall Transit Shelter are (G/G/1) (GD/∞/∞). Key words: queue process, model of queue, Semarang BRT